Proposed Legislation to Mine Brazil's Indigenous Lands Will Threaten Amazon Forests and Their Valuable Ecosystem Services - Siqueira-Gay, Juliana (One Earth, 2020)
A recent proposal to regulate mining within Indigenous Lands (ILs) threatens people and the unique ecosystems of Brazil's Legal Amazon. Here, we show that this new policy could eventually affect more than 863,000 km(2) of tropical forests—20% more than under current policies—assuming all known mineral deposits will be developed and impacts of mining on forests extend 70 km from lease boundaries. Not only are these forests home to some of the world's most culturally diverse communities, they also provide at least US $5 billion each year to the global economy, producing food, mitigating carbon emissions, and regulating climate for agriculture and energy production. It is unclear whether new mines within ILs will be required to compensate for their direct and indirect environmental and social impacts but failing to do so will have considerable environmental and social consequences.